GARBHASANSKAR -A CRITICAL REVIEW - Dr Komal Sehrawat , Dr Pragya Rohilla, Dr Latika Kaushik (EPRA International Journal of Research and Development (IJRD), 2023)
Together, Garbha and Sanskar mean shaping and cultivating the unborn while also reforming, polishing, and completing them. ’Garbha Sanskar’ is the process of choosing and disseminating beneficial influences through yoga, reading virtuous scriptures, positive thinking, prayer, healthy diet, and joyful behaviour. Your link with your child begins the moment you become pregnant, despite the fact that this may seem bizarre and weird. It’s not like you already know the baby when he’s born. Even as it is growing inside of you, the baby listens to you and is sensitive to your emotions. By meditating, rubbing your infant gently, listening to calming music, and of course thinking positively, you can influence your baby’s early impressions.